Australian bus drivers' perspectives of passenger hostility: A qualitative study. (3rd July 2022) - Ferguson, Samantha; Edwards, Elia Jade; Davis, Melanie; Racz, Jason I.; Buys, Nicholas; Bradley, Graham
Abstract: Bus drivers are at risk of the adverse impacts of passenger hostility, yet qualitative research investigating this issue is scant. We interviewed 29 bus drivers, content analyzed their responses, and interpreted findings through the prism of Demerouti et al.'s Job Demands-Resources model. Results indicated: (1) passenger hostility appeared to negatively impact driver wellbeing; (2) organizational policies may perpetuate passenger hostility; (3) support was viewed as inadequate; and (4) COVID-19 was a barrier to monitoring hostility. Findings indicate that strain associated with the demanding and poorly resourced job of bus driving is exacerbated by frequent exposure to passenger hostility.